1997
DOI: 10.1111/j.1365-2915.1997.tb00405.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plasmodium yoelii nigeriensis infection on Anopheles stephensl egg development and resorption

Abstract: It has been shown previously that infection with Plasmodium yoelii nigeriensis reduces the number of eggs produced by female Anopheles stephensi. Here we examine the mechanism underlying fecundity reduction. Ovaries from infected and uninfected (control) female mosquitoes were examined 12, 24 or 36 h after blood-feeding during the first gonotrophic cycle (replicated) or the second gonotrophic cycle (unreplicated). Follicular development was assessed according to Christophers' stages and the proportions of deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…Sporozoite infection of the salivary glands can result in increased feeding mortality when infectious [54,55]. Fecundity can be affected as smaller egg-batch size is observed due to maturing oocysts [56] but not salivary-gland sporozoites [57]. Once infectious, a mosquito's bites have a probability of infecting a human host, whether the mosquito survives the feed or dies during or after the feed.…”
Section: Methods: Model Designmentioning
confidence: 99%
“…Sporozoite infection of the salivary glands can result in increased feeding mortality when infectious [54,55]. Fecundity can be affected as smaller egg-batch size is observed due to maturing oocysts [56] but not salivary-gland sporozoites [57]. Once infectious, a mosquito's bites have a probability of infecting a human host, whether the mosquito survives the feed or dies during or after the feed.…”
Section: Methods: Model Designmentioning
confidence: 99%
“…The developmental pauses, unique pattern of hormonal secretions and discrete feeding habits of anautogenic mosquitoes have made a regulatory scheme based on nutrition production and JH synthesis more difficult to define. Thus, oosorption in mosquitoes has only been well-described after a blood meal (Carwardine and Hurd 1997; Clements and Boocock, 1984; Uchida et al, 2004); the highest rates of oosorption are seen during this time when up to 27% of follicles will become resorbed despite advanced vitellogenic development (Clements and Boocock, 1984). Follicular resorption after a blood meal can be greatly increased by Plasmodium infection in Anopheline spp .…”
Section: Introductionmentioning
confidence: 99%
“…Second, there is evidence from rodent malaria suggesting that Plasmodium induces a direct cost on female fecundity. Plasmodium yoelii induces apoptosis in mosquito ovaries [61] and increases egg resorption [62]. Although no molecule of Plasmodium origin has been identified that would justify talking about parasite manipulation, it has been widely assumed that reproductive curtailment is an adaptive strategy of the parasite to increase mosquito survival through a trade-off in energy allocation between reproduction and survival [63,64].…”
Section: (D) Mosquito Fitnessmentioning
confidence: 99%